Diptera Collectionis P. Gabriel Strobl - VI (Supplementa ad Partes I - V). - Morge, Günter (Contributions to Entomology = Beiträge zur Entomologie, 1974)
Additional information is given to parts I-V of the list of species of Strobl’s collection of Diptera.